Effect of Arginine and GA3 on Some Qualitative Traits and Active Ingredients of Matricaria chomomilla L. - Rusul Taha Ali (Academic Science Journal)
The experiment was carried out in the one fields of Saba Abcar area - north of Baghdad during winter season of 2022-2023 to study the effect of arginine and gibberellin acid on the some qualitative traits and active ingredients of chamomile plant. The experiment was designed according to randomized complete block design at three replications, the first factor included the spraying of three concentrations of arginine (0, 50 and 150 mg L-1), whereas the second factor included the spraying of three concentrations of GA3 (0, 100 and 200 mg L-1). The results showed that the spraying of arginine at a 50 mg L-1 was significantly superiority in the chlorophyll index (26.63 SPAD), carbohydrates percentage (50.38%) and volatile oil yield (13.84 Kg ha-1), while the spraying of arginine at a 150 mg L-1 was significantly superiority in the protein percentage (10.18%). Also, the results revealed that the spraying of GA3 at 100 mg L-1 was significantly superiority in the chlorophyll index (24.90 SPAD), carbohydrates percentage (50.79%) and volatile oil yield (16.30 Kg ha-1), whereas the spraying of arginine at a 200 mg L-1 was significantly superiority in the protein percentage (9.83%). The interaction between studied factors had significant effect on the all studied traits. Further, the results of HPLC analysis showed a difference in the percentages of the active ingredients of chamomile volatile oil.